Penerapan Nilai-nilai Tasawuf di Pondok Pesantren al-Fatah Temboro Magetan sebagai Upaya Menghadapi Era Globalisasi - Subhan Murtado; Ahmad Fatah Yasin (Madrasah Tsanawiyah DDI Cilellang, 2022)
The purpose of this study was to know: (1) the implementation process of the Sufism values in al-Fatah Islamic Boarding School of Temboro Magetan as an effort to face the impact of globalization; (2) supporting factors and obstacles in the implementation process; and (3) the solution provided by the Islamic boarding school when there is an obstacle in the process. This study used a qualitative approach with the case study type. The key instrument is the researcher himself, with data collection techniques used are documentation, observation, and interviews. The data was analyzed by reducing irrelevant data, describing data, and drawing conclusions. Results of the study showed that: (1) Implementation of the values of Sufism in al-Fatah Islamic boarding school of Temboro done by (a) takhalli (emptying ourselves of dependency attitude towards earthly life); (b) tahalli (filling or adorn themselves with inner and outer obedience); and (c) tajalli (unfolding curtain divider between a servant to his god). (2) factors that contribute to the implementation of values Sufism in the Islamic boarding school include: the tariqah Naqsbandiyah Khalidiyah that muktabarah, the Islamic boarding school as a center of Jama'ah Tabligh, the active role of the security department officials, the program of TABANSA (Saving Students), simplicity in life that demonstrated by the caregiver. Whereas the inhibiting factors include: the psychology students were immature, communities and families of students are less favorable. (3) Solutions provided the Islamic boarding schools in overcoming the inhibiting factors are the need for habituation to the students, the patience of the chaplain in assisting the students, and the schools impose limits for students who will be out of the boarding school environment.